The Effectiveness of Groupcounseling with Self-Management Technique to Improve Self-Efficacy and Academic Anxiety - Ardianto, Patuh; Purwanto, Edy; Awalya, Awalya (Jurnal Bimbingan Konseling, 2022)
The anxiety experienced by the students of SMK NU Hasyim Asy’ari Tarub potentially resulted in maladaptive behavior and disrupted examination preparation. Therefore, the present study strived for examining the effectiveness of group counseling with self-management technique to improve self-efficacy and reduce the anxiety of the ninth grade or class XI students in that school. Here, 20 students were involved as the subjects of this study by using a randomized pretest posttest control group design. Based on the results of paired sample t-test and independent sample t-test, this group counseling has been effective to improve the efficacy. Also, the paired sample t-test and independent sample t-test concluded that this intervention could reduce students’ academic anxiety. Finally, this study recommends the use of self-management technique to improve self-efficacy and reduce the academic anxiety of students